Influence Of Process Parameters On Farnesyl Laurate Production By Enzymatic Esterification In Packed-Bed Reactor - Rahman, Nazira Khabibor (2010)
Enzymatic esterification using lipase has proven to be potential in the production of esters. In the present work, esterification reaction in organic solvent catalyzed by immobilized lipase was studied in batch and continuous packed-bed reactor system for the synthesis of farnesyl laurate. The optimization in esterification process for both systems was carried out using design of experiment software with response surface methodology based on central composite rotatable design. Lipozyme RM IM origin from Rhizomucor miehei was found to be the most effective biocatalyst and iso-octane was considered the most suitable solvent for this esterification process since they give high molar conversion of lauric acid during screening processes.